2014
DOI: 10.1039/c4tb00876f
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-coated nano-liposomes for the oral delivery of berberine hydrochloride

Abstract: Since desirable in vitro and in vivo characteristics were achieved, chitosan-coated nano-liposomes are promising release devices for the oral delivery of berberine hydrochloride increasing the bioavailability of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 57 publications
5
84
0
6
Order By: Relevance
“…The DLS‐based size analysis confirmed that the mean droplet size of RPG‐NEs was in the ideal nanometer range of 86.5 ± 3.4 nm, with a relatively narrow particle size distribution (PDI < 0.20) suggesting that the developed NEs were suitable as carriers for oral drug delivery goals (Figure a) (Awasthi et al, ; Nguyen et al, ). In addition, RPG‐NEs revealed negative ZP values of −33.2 ± 2.6 mV, implying a sufficiently high negative surface charge assuring the enough repulsive forces between the oil droplets which, in turn, prevent any kind of breaking or coalescence, thus leading to a highly stable NE (Elsheikh et al, ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The DLS‐based size analysis confirmed that the mean droplet size of RPG‐NEs was in the ideal nanometer range of 86.5 ± 3.4 nm, with a relatively narrow particle size distribution (PDI < 0.20) suggesting that the developed NEs were suitable as carriers for oral drug delivery goals (Figure a) (Awasthi et al, ; Nguyen et al, ). In addition, RPG‐NEs revealed negative ZP values of −33.2 ± 2.6 mV, implying a sufficiently high negative surface charge assuring the enough repulsive forces between the oil droplets which, in turn, prevent any kind of breaking or coalescence, thus leading to a highly stable NE (Elsheikh et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…P188 is frequently used in pharmaceutical formulations as emulsifying, solubilizing, and dispersing agents, as well as absorbance enhancer (Hillery & Florence, 1996;Zhuang et al, 2010). Pluronics and polysorbates have been reported to increase the permeability of various drugs both in vitro and in vivo (Azmin et al, 1982;Zhang, Yao, Morrison, & Chong, 2003 Figure 2a) (Awasthi et al, 2003;Nguyen et al, 2014). In addition, RPG-NEs revealed negative ZP values of −33.2 ± 2.6 mV, implying a sufficiently high negative surface charge assuring the enough repulsive forces between the oil droplets which, in turn, prevent any kind of breaking or coalescence, thus leading to a highly stable NE (Elsheikh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated enhanced cytotoxicity in comparison to free berberine (Wen et al, 2011; Lin et al, 2014; Sailor et al, 2015). …”
Section: Liposomesmentioning
confidence: 95%
“…These liposomes can be coated with mucoadhesive polymers to increase the residence time at the ulcerated area. Some researchers have reported chitosan-coated liposomes can improve their properties and applicability 6 . First generation mucoadhesive polymers like chitosan, karaya gum etc.…”
Section: Introductionmentioning
confidence: 99%